Comparison of Oral Liposomal vs Intravenous Iron in Iron Deficiency Anemia Patients with Non-Dialysis- Dependent Chronic Kidney Disease. - Bin Khalil, Qamar; Anees, Muhammad (Pakistan Journal of Kidney Diseases, 2025)
Background: Patients with chronic Kidney disease (CKD) can receive oral or intravenous iron supplements. Liposomal iron has recently become known as a highly bioavailable alternative. Objectives: To assess and compare the efficacy of liposomal oral iron and intravenous iron in CKD patients with iron deficient anemia and not yet on dialysis . Method: CKD patients age between 18-70 years of age, not on dialysis with Hb≤10.5 and iron deficiency were enrolled. Group A received liposomal oral iron while Group B was administered 1000mg of iron sucrose intravenously over a period of 14 days. Subjects of Group A received 1.5g sachet of liposomal oral iron (containing 14mg of iron pyrophosphate) twice a day from day 0 to day 36. Results: Total 88 patients 44 in each group were included. The study revealed a significant improvement in haemoglobin level (11.07g/dL±0.41 for oral iron and 11.88g/dL±0.41 for IV iron, with a p-value of less than 0.001), ferritin level (173.20ng/ml ±13 for oral iron and 278.36ng/ml ±16.25 for IV iron, with a p-value of less than 0.001), and T-SAT level (29.15%±2.05 for oral iron and 47.66%±3.26 for IV iron, with a p-value of less than 0.001). Conclusion: According to the results of this study both iron therapies are valuable in improving Hemoglobin, and iron indices, however, IV iron therapy resulted in greater increases in hematological parameters compared to liposomal oral iron therapy. The study observed no GI, allergic or other side effects associated with liposomal oral iron and IV iron sucrose.